Palliative and supportive care in head and neck cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Cocks, H; Ah-See, K; Capel, M; Taylor, P
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It provides recommendations on the assessments and interventions for this group of patients receiving palliative and supportive care. Recommendations: Palliative and supportive care must be multidisciplinary. (G) All core team members should have training in advanced communication skills. (G) Palliative surgery should be considered in selected cases. (R) Hypofractionated or short course radiotherapy should be considered for local pain control and for painful bony metastases. (R) All palliative patients should have a functional endoscopic evaluation of swallowing (FEES) assessment of swallow to assess for risk of aspiration. (G) Pain relief should be based on the World Health Organization pain ladder. (R) Specialist pain management service involvement should be considered early for those with refractory pain. (G) Constipation should be avoided by the judicious use of prophylactic laxatives and the correction of systemic causes such as dehydration, hypercalcaemia and hypothyroidism. (G) Organic causes of confusion should be identified and corrected where appropriate, failing this, treatment with benzodiazepines or antipsychotics should be considered. (G) Patients with symptoms suggestive of spinal metastases or metastatic cord compression must be managed in accordance with the National Institute for Health and Care Excellence guidance. (R) Cardiopulmonary resuscitation is inappropriate in the palliative dying patient. (R) 'Do not attempt cardiopulmonary resuscitation' orders should be completed and discussed with the patient and/or the family unless good reasons exist not to do so where appropriate. This is absolutely necessary when a patient's care is to be managed at home. (G)